Monodispersed silk fibroin microdroplets for protein stabilization - Liu,Q; Jiang,N; Liu,D; Ying,G; Shi,Q; Yetisen,AK; Liu,H; Fan,Y (Applied Physics Letters, 2018)
Low stability of globular protein droplets in emulsion significantly limits their applications in drug encapsulation, long-term storage, and controlled drug release. Here, a microfluidic flow-focusing device was utilized to synthesize horseradish peroxidase (HRP)-loaded silk fibroin microdroplets. The two immiscible streams of microfluidic flow-focusing were regenerated by silk fibroin solution and a mixture of 95 wt. % sunflower oil and 5 wt. % span 80 as the dispersed and continuous phases, respectively. In this study, the water-in-oil silk fibroin microdroplets were homogeneously produced by leveraging the discrete and periodic breakup of microdroplets and regulating the flow rates. Moreover, the result showed that the stability of encapsulated HRP in microdroplets was 25% higher than that of HRP after 6 weeks incubation. Thus, the microfluidic flow-focusing is a promising technique to form monodisperse microdroplets and maximize the stability of protein droplets.